Gorr’s Stages in Believing in God: The Study of Illocutionary Acts - Nadilla Saffira Adma (Fakultas Ilmu Budaya, 2024)
This research deals with the analysis of the different stages in believing in Gods in the Thor: Love and Thunder movie. This thesis was conducted qualitatively. The data in this thesis were taken from the movie’s subtitles. The data were in the form of words that were considered as speech acts used by Gorr, The God Butcher who was the most super villain in the Thor: Love and Thunder movie. Those speech acts were analyzed to find out Gorr’s stages in believing in Gods and to examine the patterns in each stage. In analyzing the data, the writer uses Searle’s theory of Illocutionary Acts (1969). It was used to identify illocutionary acts in each stage and its pattern. The writer has analyzed the 73 data from the subtitle of Gorr’s utterances in Thor: Love and Thunder. Some types of illocutionary acts found in each stage. In the first stage, there were representative, directive, commissive, and expressive. In the second stage, all types of illocutionary acts were found. They were representative, directive, commissive, expressive, and declarative. In the last stage, only representative, directive, and expressive were found. Representative was mostly used in the first and the second stage. Meanwhile, directive and expressive were frequently used in the last stage. Moreover, illocutionary forces or patterns were found in each stage. The patterns of illocutionary acts that frequently used in the first stage were stating (representative) and grieving (expressive). The patterns of illocutionary acts that frequently used in the second stage were asserting, stating, and opinion, concluding (representative), questioning, confirming, and commanding (directive). The patterns of illocutionary acts that frequently used in the third stage were asserting (representative) and questioning (directive). Looking at the findings, Gorr mostly committed to deliver some facts and his belief to the listeners in the first stage. Besides he did not only deliver his belief, he also commanded Thor and Valkyrie as he pleased in the second stage. However he appreciated another human by appreciating Axl’s story, one of the Asgardian kids, even though he was known as The God Butcher at this stage. In the last stage, Gorr was shown more expressive by how he expressed love and regret to his daughter. He requested Thor to protect his daughter when he was gone. The representative type was also used in this stage by Gorr asserted his worth as a father if he would stop his revenge to Gods
Keywords: Gorr’s Stages in Believing in God; The Study of Illocutionary Acts